Led Zeppelin : the Illustrated Biography - Illustrated Biography by Thomas, Gareth (Croxley Green, Hertfordshire Transatlantic Press, 2009)
Through a combination of stunning photographs and insightful captions, this book chronicles the meteoric rise to fame of one of the world's biggest bands, from their roots in the British Blues scene, through the highs and lows and the success and excesses of stardom to assume their rightful place in the pantheon of rock & roll.
Include colour illustrations
Keywords: Rock musicians -- Led Zeppelin (Musical group) -- Rock groups